Impact of Digital Transformation, Differentiation Strategy, and Innovation Capability on Competitive Advantage: Survey of Beverage MSMEs in Sukabumi City) - Noval, Muhammad; Danial, R. Deni Muhammad; Saori, Sopyan (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the influence of Digital Transformation, Differentiation Strategy, and Innovation Capability on Competitive Advantage in beverage MSMEs in Sukabumi City. The respondents in this study were 100 beverage MSMEs in Sukabumi City. This research employed a quantitative method with a descriptive and associative approach. The statistical tests used in this study included simultaneous testing (F-test) and partial testing (t-test). The results of the study indicate that there is a positive and significant simultaneous influence of Digital Transformation, Differentiation Strategy, and Innovation Capability on Competitive Advantage, as evidenced by the F-count value of 13,416 > F-table 3,096. Partially, Digital Transformation does not have a significant positive effect on Competitive Advantage, as shown by the t-count value of 1.152 with a significant value of 0.252 > 0.05. Meanwhile, Differentiation Strategy has a positive and significant effect on Competitive Advantage, which is proven by the t-count value of 4.312 with a significance value of 0.000 < 0.05. Furthermore, Innovation Capability also has a positive and significant effect on Competitive Advantage, with a t-count value of 2.891 and a significance value of 0.005 < 0.05.